Meningkatkan Kemampuan Motorik Halus Melalui Aktivitas Melipat Kertas Pada Anak Usia 5-6 Tahun di PAUD Kober Melati III Kecamatan Waluran Kabupaten Sukabumi - Marsela, Anis; Awal Maulana, Redi; Elnawati, Elnawati (PT. Alahyan Publisher Sukabumi, 2025)
When children start folding paper, they can learn to fold their own clothes or simple objects. They can also learn to recognize shapes when they make shapes out of paper. The results of initial observations can be stated that children's motor skills are currently only around 17.7% or as many as 3 children in the category of children developing according to expectations (BSH) while children in the Very Well Developing category have not yet appeared, and the level scores of children in the Not Yet category are still high. Capable is 58.8% or as many as 10 children, while 4 children or 23.5% are still included in the category of children starting to develop (MB). The aim of this research is that researchers want to improve children's fine motor skills through paper folding activities. The method used in this research is the classroom action research method using research subjects, namely 17 children aged 5-6 years in KOBER Melati III Sukabumi Regency. Paper folding activities can improve the fine motor skills of children aged 5-6 years at PAUD KOBER Melati III, Waluran District, Sukabumi Regency. The explanation in the previous chapter shows that children's fine motor skills are getting better. The target completeness value in this research was 75%, and the paper folding method value was 82%.